2022
DOI: 10.3389/fnhum.2022.1079596
|View full text |Cite
|
Sign up to set email alerts
|

Surface electromyography analysis of mirror movements under unilateral movement in stroke patients: A retrospective study

Abstract: ObjectiveMirror movements (MMs) are common abnormal motor performance in patients with poststroke hemiparesis. The study aimed to utilize the Electromyography (EMG) characterization of MMs in stroke patients and explore the relationship between MMs and the motor function of affected limbs.MethodsSixty patients with stroke who had used to undergo clinical assessment and surface Electromyography (sEMG) were selected in this study. We investigated the standardized net excitation (SNE) and overflow percentage (OF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition, it has been suggested that motor overflow may be a clinical indicator of the recovery process of motor function after stroke. In addition, a correlation between motor overflow occurring on the nonoperating side and muscle activity on the operating side has been reported for unilateral upper limb movements after stroke [40]; in this study, EMG was used to assess motor overflow in 60 patients with stroke. The participants performed unilateral elbow flexion exercises for 5 seconds on both sides.…”
Section: Central Nervous Disorders and Motor Overflowmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, it has been suggested that motor overflow may be a clinical indicator of the recovery process of motor function after stroke. In addition, a correlation between motor overflow occurring on the nonoperating side and muscle activity on the operating side has been reported for unilateral upper limb movements after stroke [40]; in this study, EMG was used to assess motor overflow in 60 patients with stroke. The participants performed unilateral elbow flexion exercises for 5 seconds on both sides.…”
Section: Central Nervous Disorders and Motor Overflowmentioning
confidence: 96%
“…Figure 2.Comparison between OF′AEMG and OF′RMS of bilateral biceps brachii during a unilateral contraction task[40]. AEMG represents the mean amplitude of the electromyography waveform.…”
mentioning
confidence: 99%
“…Eleven articles studied UE asymmetry during indirect periodic movements (e.g., gait, etc.) [106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121]. Some excluded studies were designed to assess a specific device's design [122][123][124][125], focused on mathematical modelling and analysis of the asymmetries [111,[126][127][128][129][130], or did not study the UE asymmetry resulting from any specific neurological condition (e.g., ).…”
Section: Selection Of Sourcesmentioning
confidence: 99%